Economic incentives for indirect TTIP spillovers - Lejour, Arjan M.; Mustilli, Federica; Pelkmans, Jacques; Timini, Jacopo (Brussels, 2014)
"A deep, comprehensive and ambitious TTIP should not undermine or otherwise negatively affect the WTO and its signatories. Among other things, this means that trade diversion ought to be minimised and positive spillovers stimulated. The present CEPS Special Report provides some elementary quantification, which helps to understand the economic incentives for third countries to seek regulatory alignment with TTIP results, where relevant, and for which TTIP should be ‘open’. It focuses on ‘indirect’ spillovers and employs a rather aggregate economic approach. We find that, of three groups of countries that are important for trade with the EU and the US, the ‘closest’ neighbours (NAFTA, EEA, Switzerland and Turkey) exhibit powerful incentives to align so as to benefit from positive spillovers. This is less clear for two other groups. Of the (seven) ‘biggest traders’ (in manufactured goods, for which spillovers matter most), China turns out to have the greatest interest in alignment in selected sectors, followed by Israel, Japan and South Korea. Whereas the latter three either have or are negotiating FTAs with the US and the EU, precisely China has none and remains outside TPP as well. In terms of sectors, the chemical sector followed by electronic equipment are by far the most important, with agro-products and fish as a good third (SPS issues). However, in chemicals and electrical equipment, the TTIP negotiations so far, and recent US/EU regulatory cooperation, do not indicate an ambitious approach, which could reduce regulatory barriers to market access drastically."